2019
DOI: 10.1002/ana.25455
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apolipoprotein E4 increases cell death and phosphorylated tau release in alzheimer disease

Abstract: Objective:The apolipoprotein E (APOE) E4 isoform is the strongest genetic risk factor for sporadic Alzheimer disease (AD). Although APOE is predominantly expressed by astrocytes in the central nervous system, neuronal expression of APOE is of increasing interest in age-related cognitive impairment, neurological injury, and neurodegeneration. Here, we show that endogenous expression of E4 in stem-cell-derived neurons predisposes them to injury and promotes the release of phosphorylated tau. Methods: Induced plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 70 publications
5
62
0
Order By: Relevance
“…Apart from Aβ, evidence from recent studies suggests that apoE in uencing tau pathology and taumediated neurodegeneration is also in an isoform-dependent manner [60,61]. Furthermore, apoE ε4 accumulation impairs glial responsiveness, lipid transport and cerebrovascular integrity and function, which might be independent of Aβ-related pathways [31,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from Aβ, evidence from recent studies suggests that apoE in uencing tau pathology and taumediated neurodegeneration is also in an isoform-dependent manner [60,61]. Furthermore, apoE ε4 accumulation impairs glial responsiveness, lipid transport and cerebrovascular integrity and function, which might be independent of Aβ-related pathways [31,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The first identified SAD risk factor, APOE4 has been the most studied risk mutation in iPSC-derived cells, as it has been in rodent and other models. iPSCderived neurons carrying APOE4 produce more Aβ and have higher levels of tau phosphorylation compared to APOE3 cells [35,38,39,110,114]. Surprisingly, elevated p-tau levels were not dependent on Aβ in APOE4 cells, indicating perturbation of additional pathways regulating tau phosphorylation [39].…”
Section: Human Neural Progenitor Cell and Neuron Modelsmentioning
confidence: 98%
“…CRISPR/Cas9 has already been proven successful in iPS cells, where cells derived from a healthy E3/E4 individual were converted into E2/E2, E3/E3, E4/E4, or an APOE KO genotype [157]. A second group used iPS cells derived neurons from an APOE4 carrier and found that CRISPR-editing the APOE4 reduced tau phosphorylation and inomycin-induced cell death [158]. Interestingly, though in the CNS APOE is mostly synthesized by astrocytes, this study showed that editing neuronal APOE to the E3 isoform in these iPS-derived neurons is sufficient to protect them from cytotoxic injury [158].…”
Section: Crispr/cas9 Mediated Gene Editingmentioning
confidence: 99%
“…A second group used iPS cells derived neurons from an APOE4 carrier and found that CRISPR-editing the APOE4 reduced tau phosphorylation and inomycin-induced cell death [158]. Interestingly, though in the CNS APOE is mostly synthesized by astrocytes, this study showed that editing neuronal APOE to the E3 isoform in these iPS-derived neurons is sufficient to protect them from cytotoxic injury [158]. Another study generated different brain cell types and organoids from iPS cells derived from a human subjecton editing the APOE4 allele to APOE3 in these iPS-derived cells increased Aβ clearance and reduced Aβ in the organoid cultures [49].…”
Section: Crispr/cas9 Mediated Gene Editingmentioning
confidence: 99%